Autistic disorder with complex IV overactivity: A new mitochondrial syndrome - Frye, Richard E.; Naviaux, Robert K. (Journal of Pediatric Neurology, 2011)
Although mitochondrial disease is usually associated with reductions in electron transport chain complex activity, a few reports have associated mitochondrial disease with complex overactivity. This is the first report to associate complex IV overactivity with autistic disorder. Five patients with a significant elevation in complex IV activity, abnormal muscle electron microscopy and autistic disorder with developmental regression are reported. The majority, 80%, manifested either epilepsy or subclinical epileptiform discharges on electroencephalogram. Cerebral folate deficiency was found in the three patients evaluated for this disorder. The majority of patients had potentially detrimental nuclear and mitochondrial abnormalities. This series represents a new mitochondrial syndrome characterized by autistic disorder with complex IV overactivity. The association with cerebral folate deficiency is important as cerebral folate deficiency is treatable with folinic acid. The significance of an increase in complex IV function is discussed in the context of the associated physiological disturbances reported in autism spectrum disorder.
Keywords: Autism; complex IV; mitochondrial dysfunction; mitochondrial DNA mutation; regression